Evaluation of antimicrobial and antioxidant efficiency and phytochemical screening of Azadirachta indica leaves - Al-Abyadh, Mokhtar (LAP Lambert Academic Publishing, 2019)
Evaluate antimicrobial and antioxidant efficiency and phytochemicalscreening of Azadirachta indica leafs. The antimicrobial analysis of leaves extracts of Azadirachta indicawas determined by using well Diffusion Methods that showed that theextracts inhibit the action of S.aureus (19.49mm), E.coli (11.49mm) inchloroform; S.aureus(19.84mm), P. aeruginosa(17.57mm) and E.coli(12.24mm) in Ethanol; While the aqueous extract showed (42.57mm) inM.gypseum, P. aeruginosa (18.40mm), E.coli (17.09mm), S.aureus(14.44mm) and K. pneumonia(12.84mm); while they had no action on P.aeruginosa and M.gypseum in chloroform extract and K. pneumonia andM.gypseum in Ethanol extract. Then, the antioxidant activity wasidentified by using DPPH method with a Qualitative activity (TLCautography method). It showed that all extracts have antioxidantactivities. In quantitative test the antioxidant activity was showedthe maximum of DPPH Inhibition in Ethanol extract (84.537) ; While theminimum of DPPH Inhibition showed in chloroform(46. 466). DPPH andascorbic acid were used as standard.